Three-dimensional transition and force characteristics of low-Reynolds-number flows past a plunging airfoil - Gao, An-Kang; Cantwell, Chris D.; Son, Onur; Sherwin, Spencer J. (Cambridge Univ Press, 2023)
The three-dimensional (3-D) transition of the leading-edge vortex (LEV) and the force characteristics of the plunging airfoil are investigated in the chord-based Strouhal number St(c) range of 0.10 to 1.0 by means of experimental measurements, numerical simulations and linear stability analysis in order to understand the spanwise instabilities and the effects on the force. We find that the interaction pattern of the LEV, the LEV from a previous cycle (pLEV) and the trailing-edge vortex (TEV) is the primary mechanism that affects the 3-D transition and associated force characteristics. For St(c) <= 0.16, the 3-D transition is dominated by the LEV-TEV interaction. For 0.16 < St(c )<= 0.44, the TEV lies in the middle of the LEV and the pLEV and therefore vortex interaction between them is relatively weak; as a result, the LEV remains two-dimensional up to a relatively high Reynolds number of Re = 4000 at St(c) = 0.32. For 0.44 < St(c) <= 0.54, and at relatively low Reynolds numbers, the pLEV and the TEV tend to form a clockwise vortex pair, which is beneficial for the high lift and stability of the LEV. For 0.49 <= St(c), the pLEV and TEV tend to form an anticlockwise vortex pair, which is detrimental to the lift and flow stability. In the last St(c) range, vortex interaction involving the LEV, the TEV and the pLEV results in an unstable period-doubling mode which has a wavelength of about two chord-lengths and the 3-D transition enhances the lift.
Keywords: vortex instability; vortex interactions